Anaesthetic management of paediatric adenotonsillectomy - L. Strauss (South African Family Practice)
Tonsillectomy with or without adenoidectomy is one of the most frequent surgical procedures that are carried out globally. Although these children are often fit, anaesthesia for such cases can be associated with significant morbidity and mortality, and should not be undertaken lightly. An approach to the anaesthetic management of paediatric adenotonsillectomy is presented.